Clinical, Laboratory and Radiologic Evaluations in Patients with Malignant Tuberculous Spondylitis - Bambang Prijambodo1 , Udria Satya Pratama2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Tuberculous spondylitis patient diagnosis still becomes a challenging task in orthopedics.Mycobacterium tuberculosis Beijing strain caused malignant tuberculous spondylitis in most patients(66.7%). Therefore, they proposed scoring system to estimate the prognosis of patients with malignanttuberculous spondylitis with some parameters, including abscess area, erythrocyte sedimentation rate (ESR),number of vertebral destruction, disseminated tuberculosis and infectious Mycobacterium tuberculosis stain.Objectives: To perform clinical, laboratory and radiologic evaluations in patients with malignant tuberculousspondylitis using scoring system proposed by Yunus and PrijambodoMethods: This retrospective cohort study was carried out from 2012 to 2015 in patients with malignanttuberculous spondylitis at Dr. Soetomo Teaching Hospital, Surabaya, Indonesia, using Yunus and Prijambodoscoring. Subjects were evaluated in minimum 6 months after surgery. The evaluations included clinical(abscess recurrence), laboratory (ESR) and radiologic (bony fusion in spinal X-ray tomography).Results: Of eight acute tuberculous patients, only 5 were evaluated. One had moderate prognosis and fourhad severe prognosis. No abscess recurrence found in patients after 20-month evaluation. ESR was below20 mm/hour (12.8±7.8) and 80% of patients had bony fusion in spinal X-ray tomography.Conclusion: Most patients with malignant tuberculous spondylitis with moderate and severe prognosishad better outcomes after 20-month evaluation. Further studies should consider other factors affectingtuberculous spondylitis patient’s prognosis including host factor.